Altemeier Procedure (Perineal Rectosigmoidectomy) for Incarcerated and 41 Recurrent Rectal Prolapse - Ismail, Fahmi; Sainal, Mohd. Yusof; Elagili, Faisal; Md Nor, Azmi (2020)
OBJECTIVE We describe a rare case of incarcerated, recurred rectal prolapse and was managed successfully with perineal proctosigmoidectomy. CASE REPORT A 71 year old woman with hypertension and parkinsonism underwent successful perineal stapled prolapse resection. Two months later she presented with incarcerated recurrent rectal prolapse. On clinical examination, vital signs within normal limits. Her abdomen was not tender and had no signs of peritoneal irritation. Rectal examination revealed 10 cm incarcerated prolapsed rectum with markedly swollen, congested, and showed signs of superficial mucosal erosion and necrosis. Because of patient’s age, comorbidities, failure of external manual reduction and the appearance of established necrosis, we decided to proceed with perineal proctosigmoidectomy. The postoperative recovery was uneventful and the patient discharged on the fourth day. Histopathological examination revealed necrosis of mucosa and submucosa in resected specimen. During subsequent clinic follow-up 3 months later noted no evidence of recurrent rectal prolapse. CONCLUSION Our patient successful treatment with perineal proctosigmoidectomy (Altemeier’s procedure), highlights the value of this procedure in debilitated elderly patient with incarcerated recurrent rectal prolapse.